Fältinstruktion för skogsbruksplanering av inhemska skogar i Andinska Patagonien - Sjödin, Fredrik (SLU/Dept. of Forest Resource Management, 2008)
The thesis first objective was to develop field instructions for forest planning of native forests in Andean Patagonia, and the second objective was to test the plan on an actual property in the area. The thesis was limited to studies in the province of Rio Negro. Today, there are no official forest management plans for native forests in the Argentinean province of Rio Negro; thus, there is an obvious need for an official forest management plan with clear guidelines. To be granted permission to manage, i.e. through thinning, the native forests on a property it is required to have a forest management plan that is approved by the Forestry Board in the province in question (Thill, B. 2006/2007).